Adipocentric origin of the common cardiometabolic complications of obesity in the young up to the very old: pathophysiology and new therapeutic opportunities - Sarzani, Riccardo; Landolfo, Matteo; Di Pentima, Chiara; Ortensi, Beatrice; Falcioni, Paolo; Sabbatini, Lucia; Massacesi, Adriano; Rampino, Ilaria; Spannella, Francesco; Giulietti, Federico (Frontiers in Medicine, 2024)
Obesity is a multifactorial chronic disease characterized by an excess of adipose tissue, affecting people of all ages. In the last 40 years, the incidence of overweight and obesity almost tripled worldwide. The accumulation of "visceral" adipose tissue increases with ageing, leading to several cardio-metabolic consequences: from increased blood pressure to overt arterial hypertension, from insulin-resistance to overt type 2 diabetes mellitus (T2DM), dyslipidemia, chronic kidney disease (CKD), and obstructive sleep apnea. The increasing use of innovative drugs, namely glucagon-like peptide-1 receptor agonists (GLP1-RA) and sodium-glucose cotransporter-2 inhibitors (SGLT2-i), is changing the management of obesity and its related cardiovascular complications significantly. These drugs, first considered only for T2DM treatment, are now used in overweight patients with visceral adiposity or obese patients, as obesity is no longer just a risk factor but a critical condition at the basis of common metabolic, cardiovascular, and renal diseases. An adipocentric vision and approach should become the cornerstone of visceral overweight and obesity integrated management and treatment, reducing and avoiding the onset of obesity-related multiple risk factors and their clinical complications. According to recent progress in basic and clinical research on adiposity, this narrative review aims to contribute to a novel clinical approach focusing on pathophysiological and therapeutic insights.